Isolation and characterisation of free-living nitrogen fixing bacteria from soil environment - Kong, Chia Huoi (2024)
Biological nitrogen fixation is a vital process in the nitrogen cycle which is performed by diazotrophs. Diazotrophs use nitrogenase enzymes to catalyse the conversion of dinitrogen gas into ammonia, which can be absorbed by plants. This present study aimed to isolate and characterise the free-living nitrogen fixing bacteria from the soil samples collected in Kampar. The locations involved were Zone F and Zone P in the UTAR Kampar campus as well as Eastlake areas. The nitrogen fixing bacteria from the collected soil samples were isolated using Burk’s medium. The bacterial isolates were characterised through Gram staining and the Gram-negative bacterial isolates were subjected to selected biochemical tests for the identification of Enterobacteriaceae. All the twenty bacterial isolates were screened for the nifH gene, but only three of them showed an approximate 360 bp amplicon after the PCR amplification using nifH primers. As such, the three bacterial isolates, N-6, E-I, and E-VI were selected for 16S rRNA sequencing, and the BLASTN results showed that they were identified as Bacillus luciferensis, Dickeya zeae, and Kosakonia oryzendophytica, respectively. However, the BLASTX results showed that the nifH gene was only present in E-I and E-VI.